Pengaruh Lingkungan Geografi Terhadap Pengembangan Pariwisata Ekonomi Di Kota Surakarta - Lilik Sofianiyatin (Investama : Jurnal Ekonomi dan Bisnis, 2020)
Surakarta City has potential tourism objects such as Surakarta Hadiningrat Palace, Pura Mangkunegaran, Radya Pustaka Museum, Sriwedari People's Entertainment Park (THR), Taman Balekambang, Taru Jurug Wildlife Park (TSTJ), and others. This research discusses three objects, including Surakarta Hadiningrat Palace, Sriwedari People's Entertainment Park (THR) and Taru Jurug Animal Park (TSTJ) because it is more popular with visitors (Surakarta City Culture and Tourism Office, 2008-2011) and potential. Based on the observation of the object the condition is not maintained and the facilities are not yet complete. This study takes the title THE EFFECT OF GEORAFI ENVIRONMENT ON TOURISM DEVELOPMENT IN SURAKARTA which aims to determine the classification of the internal and external potential of tourism objects, determine the priority of tourism development, and find out the direction of tourism development in Surakarta City. TSTJ was developed by combining zoos and playgrounds, utilizing the Bengawan Solo River and artificial lakes as a relaxing area by adding buildings to enjoy the surrounding objects. THR Sriwedari was developed into a bigger and more complete amusement park because this object is expected to attract more visitors. The Surakarta Hadiningrat Palace does not need to carry out development that is changing or adding (pattern / structure) with the exception of repairs to damaged buildings and has to be replaced because of its appeal to existing relics including buildings. This object requires care by maintaining the cleanliness of objects and collections and maximizing tourism facilities.